The effect of low sulphur wax residique (LSWR) and sorbitan monooleate (SPAN-80) to the emulsion fuel stability - Muhammad Kharin Annuar, Sairan (2013)
The world oil resources are getting low daily. However, the usage still increasing due to the technology advancement nowadays. Yet, the world still did not find any suitable replacement for this resource which can give high energy at affordable cost, also it must be easy to use by all people. The most efficient resource of energy that can be replacing oil is nuclear power. Nuclear power has it all, efficient, clean, long lasting, but the downside is not every country has ability to build this technology and it is considered as a highly dangerous source of energy as it produces not only explosion but also radiation. Then this study was conducted to give more time for oil energy era before it become completely extinct. More time for the world to find an efficient source of energy that can be used by the people like this oil energy. The basic of this study is to create a combination of oil and water as an emulsion fuel. Oil and water are immiscible due to polar molecule having in the water. They need some element that can combine and stabilize them together and that element is the emulsifier. Emulsifier functioning as a binding element for the diesel and water to combine, the emulsifier used in this study are Span-80 and LSWR. The materials used in this study were Diesel oil, water, Span-80 and LSWR. This study consists of two parts, finding suitable ratio and analyzing characterization. For finding suitable ratio, 20:80, 30:70 and 40:60 of water in oil ratio with 1%, 1.5% and 2% emulsifier percentage each, were used. By using a propeller the oil were agitated with the emulsifier for about 5 minutes at 2000 rpm, then the water slowly poured into the solution and agitated more for 10 minutes. The emulsion fuel then putted into a measuring cylinder and take the stability data at 3, 6, 24, 48 and 120 hours. For analyzing characterization, the water droplets size was checked with microscope lOx lens, viscometer to check shear rate,. shear stress, viscosity. From the study, Span-80 emulsifier is more stable than LSWR. Based from data for 20:80 water in oil and using 1.5% emulsifier. For SPAN-80 about 73.5% of emulsion fuel, maintain its state after 120 hours. The rest, 1 .5% turned into oil and 25% turned into oil in water layer.Differently for LSWR about 80.6% of the emulsion fuel, maintain its state after 120 hr. However, almost 38 mL from 40 mL of water was dispersed at the bottom layer. Meaning the LSWR has high ability to hold most of the oil but not the water.